(untitled) (Research, Society and Development, 2022)
This research aimed to evaluate human thermal comfort in two informal settlements in the city of São Luís - Maranhão in 2020, a period characterized by measures of isolation and physical distancing. To measure the thermal comfort zones of the local inhabitants, the hourly method of degrees-day was used through the equations of DeDear and Brager and Humphreys, and the Normalized Difference Vegetation Index (NDVI) and the Terrestrial Surface Temperature (TST), obtained by through orbital imaging. The results of these equations indicate that there was no need for cooling on any day of the year analyzed. For most of the period, the days were characterized by a comfortable thermal zone, with emphasis on some days with the need to increase the air temperature to improve the thermal sensation of comfort in the urban area of São Luís. However, the results of the spatial distribution of the TST show high temperatures close to 30°C (degrees Celsius) in areas of urban densification, confirmed by the mapping of land use and land cover in the region, obtained through the NDVI. These high values are due to the local changes that have taken place with the use of building materials that absorb much of the radiant energy and heat up residential environments, causing uncomfortable thermal sensations. In these areas it is necessary to adopt measures of thermal attenuation so that the environment becomes more comfortable.